Global adiposity rather than abnormal regional fat distribution characterizes women with polycystic ovary syndrome. - Barber, T; Golding, S; Alvey, C; Wass, J; Karpe, F; Franks, S; McCarthy, M (2008)
CONTEXT: Obesity-related predisposition to polycystic ovary syndrome (PCOS) could reflect overall adiposity and/or regional accumulation of abdominal visceral fat. OBJECTIVE: The objective of the study was to compare distributions of visceral, abdominal sc, and gluteofemoral sc adipose tissue in PCOS cases vs. control women. DESIGN: This was a cross-sectional study. SETTING AND PARTICIPANTS: Fat depot measurements from axial magnetic resonance imaging scans taken at anatomically predefined sites were compared between 22 body mass index (BMI)/fat mass-matched pairs of PCOS cases and controls; whole-group comparisons included 50 PCOS cases vs. 28 female controls. All subjects were of UK British/Irish origin. MAIN OUTCOME MEASURE(S): We measured cross-sectional areas of adipose tissue within visceral (mid-L4), abdominal (mid-L4) sc, and gluteofemoral (greater trochanteric and midfemoral) sc fat depots. Other measurements included fat mass, BMI, testosterone, SHBG, and homeostasis model assessment of insulin resistance (a measure of insulin sensitivity). Whole-group analyses were adjusted for fat mass and age. RESULTS: There were no significant differences in fat-depot measurements between BMI/fat mass-matched pairs of PCOS cases and controls: mid-L4 visceral (P=0.40), abdominal sc (P=0.22), gluteal sc (P=0.67), and midfemoral sc (P=0.37) depots. Whole-group comparisons gave similar results after adjustments for fat mass and age. Fasting serum insulin concentrations (P=0.03) and homeostasis model assessment of insulin resistance (P=0.03) were significantly higher in the PCOS group than BMI/fat mass-matched controls. CONCLUSIONS: PCOS cases and BMI/fat mass-matched control women are indistinguishable with respect to distribution of fat within visceral, abdominal sc, and gluteofemoral sc depots, despite significant differences in insulin resistance between these two groups.